Crystallization and preliminary X‐ray analysis of the C‐terminal fragment of Ski7 from Saccharomyces cerevisiae. Issue 9 (1st September 2014) - Lee, Ji‐Young; Park, Si Hoon; Jeong, Byung‐Cheon; Song, Hyun Kyu
Abstract : Ski7 (superkiller protein 7) plays a critical role in the mRNA surveillance pathway. The C‐terminal fragment of Ski7 (residues 520–747) from Saccharomyces cerevisiae was heterologously expressed in Escherichia coli and purified to homogeneity. It was successfully crystallized and preliminary X‐ray data were collected to 2.0 Å resolution using synchrotron radiation. The crystal belonged to a trigonal space group, either P 31 21 or P 32 21, with unit‐cell parameters a = b = 73.5, c = 83.6 Å. The asymmetric unit contains one molecule of the C‐terminal fragment of Ski7 with a corresponding crystal volume per protein mass ( V M ) of 2.61 Å 3  Da −1 and a solvent content of 52.8% by volume. The merging R factor is 6.6%. Structure determination by MAD phasing is under way.